Strategic Segmentation of the Spanish Electrical Material Distribution Industry based on Economic and Financial Indicators - Pons-Verdú, Fernando José (2023)
The effectiveness of strategic decisions depends, to a large extent, on the precision with which one knows one's own positioning and that of competitors. At present, the economic-financial information of almost any industry is abundant. However, most industry studies offer values ​​that are not always applicable to the particular analysis of a company. Companies in the electrical equipment distribution sector in Spain exceed 5,000 million euros in sales and present a high degree of heterogeneity in size and strategy. Based on the theory of strategic groups, this paper proposes a method of analysis and segmentation of an industry using exclusively economic-financial information. The results obtained make it possible to identify the existing strategic groups in the industry, as well as the strengths and weaknesses of the company in relation to its "real" competitors. This information is expected to guide business decision-making towards the defensive and prospective actions necessary to improve its competitive position in the sector and in its strategic group.